Identifying the Impact of Road Networks on Forest Land Using Geographical Information System and Remote Sensing: A Case Study of Teknaf Reserved Forest (Journal of Bangladesh Institute of Planners, 2012)
The aim of this study is identifying impact of road networks on forest land. Teknaf Reserved Forest area was selected for case study. To make the study forest land class was defined using remote sensing (RS) analysis. Then evaluation on changes of forest coverage was made using GIS analysis tools. The study results were validated by conducting interviews with local stakeholders. The study finds that within a reasonable visible range there is no impact of metal road on forest land, while, the impact of footpath is highest. It also shows that decreasing rate of forest land due to all type of roads is lower than that of all over the study area.Journal of Bangladesh Institute of Planners Vol. 5, Dec 2012, pp. 199-203